Polish Independent Press Review, no. 12 (1988) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Topical reviews of Polish samizdat publications in English prepared by RFE staff members to be used by different national broadcasting units. PIPR was published from 1986 until November 1989 as a continuation of Polish Underground Extracts (PUE). Ethnic Minorities in Poland Press Their Rights / by Anna PomianSeveral representatives of ethnic minorities living in Poland recently addressed their demands to Lech Wałęsa. Solidarity has pledged to defend their interests in any future negotiations with the Polish authorities. Initial Reactions to the Closure of the Gdańsk Shipyard / by Anna PomianPolish independent writers have tended to view the announcement of the closure of the Gdańsk Shipyard as a political provocation aimed at Solidarity. "Eastern Archive": A New Documentation Center / by Anna PomianAn independent documentation center with branches in several Polish cities has been set up to research into the lives of Poles returning to Poland after having been deported to the Soviet Union. Polish Self-sufficiency on the Increase / by Anna PomianThe deteriorating material situation of most Poles has forced them to rely on their own personal resources to an increasing extent and to find novel ways of making ends meet. Profiles of Major Independent Polish Publications: "Kurs: Niezależny Miesięcznik Literacki" / by Witold Pronobis"Kurs" is a literary monthly that has been appearing in Warsaw since 1983.